2019
DOI: 10.3389/fneur.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Course in Chronic Subdural Hematoma Patients Aged 18–49 Compared to Patients 50 Years and Above: A Multicenter Study and Meta-Analysis

Abstract: Objective: Chronic Subdural Hematoma (cSDH) is primarily a disease of elderly, and is rare in patients <50 years, and this may in part be related to the increased brain atrophy from 50 years of age. This fact may also influence clinical presentation and outcome. The aim of this study was to study the clinical course with emphasis on clinical presentation of cSDH patients in the young (<50 years). Methods: A retrospective review of a population-based cohort of 1,252 patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…One patient was excluded due to having acute-on-chronic presentation. Of 90 total identified cSDH patients, 31 were deceased during the follow-up period, which is consistent with mortality rates in other published series,[ 2 ] and another 9 patients were ineligible due to aforementioned criteria.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…One patient was excluded due to having acute-on-chronic presentation. Of 90 total identified cSDH patients, 31 were deceased during the follow-up period, which is consistent with mortality rates in other published series,[ 2 ] and another 9 patients were ineligible due to aforementioned criteria.…”
Section: Resultssupporting
confidence: 85%
“…found 32% mortality rate at 12 months in elderly cSDH cohort with a mean age of 80. [ 2 ] Another study comparing the immediate postoperative period in patients below and above age 50 found that the older group had higher rates of surgical complications during evacuation of cSDH and during recovery. [ 6 ] Stippler et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical factors related to RrR were retrospectively analyzed in this study. As reported previously, age (> 65 years) was related to recurrence 3,12 . The imaging characteristics during the perioperative period play an important role in the assessment of the RrR.…”
Section: Discussionsupporting
confidence: 78%
“…Young patients most often present with signs of increased intracranial pressure, such as progressive headache, nausea, and vomiting. 10,11 In older patients, ‡65 years of age, cognitive and mental changes are more prevalent. 12,13 In past decades, most studies on CSDH focused on surgical techniques, risk factors for the development of CSDH, perioperative use of anticoagulants, or optimal treatment modalities.…”
Section: Introductionmentioning
confidence: 99%